Regional Variation in Identified Cancer Care Needs of Early‐Career Oncologists in China, India, and Pakistan. (17th April 2015) - Lyerly, H. Kim; Fawzy, Maria R.; Aziz, Zeba; Nair, Reena; Pramesh, C.S.; Parmar, Vani; Parikh, Purvish M.; Jamal, Rozmin; Irumnaz, Azizunissa; Ren, Jun; Stockler, Martin R.; Abernethy, Amy P.
Abstract : Background: Cancer incidence and mortality is increasing in the developing world. Inequities between low‐, middle‐, and high‐income countries affect disease burden and the infrastructure needs in response to cancer. We surveyed early‐career oncologists attending workshops in clinical research in three countries with emerging economies about their perception of the evolving cancer burden. Methods: A cross‐sectional survey questionnaire was distributed at clinical trial concept development workshops held in Beijing, Lahore, Karachi, and Mumbai at major hospitals to acquire information regarding home‐country health conditions and needs. Results: A total of 100 respondents participated in the workshops held at major hospitals in the region (India = 29, China = 25, Pakistan = 42, and other = 4). Expected consensus on many issues (e.g., emergence of cancer as a significant health issue) was balanced with significant variation in priorities, opportunities, and challenges. Chinese respondents prioritized improvements in cancer‐specific care and palliative care, Indian respondents favored improved cancer detection and advancing research in cancer care, and Pakistani respondents prioritized awareness of cancer and improvements in disease detection and cancer care research. For all, the most frequently cited opportunity was help in improving professional cancer education and training. Conclusion: Predominantly early‐career oncologists attending clinical research workshops (in China, India, and Pakistan) identified needs for increasing clinical cancer research, professional education, and public awareness of cancer. Decision makers supporting efforts to reduce the burden of cancer worldwide will need to factor the specific needs and aspirations of health care providers in their country in prioritizing health policies and budgets. Abstract : A cross‐sectional survey questionnaire was distributed at clinical trial concept development workshops held at major hospitals in Beijing, Lahore, Karachi, and Mumbai to acquire information regarding home‐country health conditions and needs. The respondents were predominantly early‐career oncologists who identified needs for increasing clinical cancer research, public awareness of cancer, and especially professional cancer education and training. Abstract : 摘要 背景 . 发展中世界的癌症发生率和死亡率持续升高。低、中、高收入国家之间的不公平影响着癌症造成的疾病负担和对基础设施的需求。我们对三个新兴经济体国家中参加临床研究研讨会的年轻肿瘤科医生就关于癌症负担演变的看法开展了调查。 方法 . 在北京、拉合尔、卡拉奇和孟买的大医院召开的临床试验发展观研讨会上发放横断面调查问卷，以获得回答者祖国卫生保健状况和需求方面的信息。 结果 . 在当地大医院举办的研讨会的参与者中，共有100名应答者（印度29名，中国25名，巴基斯坦42名，其他国家或地区4名）。在许多问题上获得了预期的共识（如发生癌症是严重的健康问题），与此同时，在优先排序、机遇及挑战方面各国应答者之间则有明显差异。中国应答者将改善癌症专科治疗和姑息治疗的优先级排在首位，印度应答者将提高癌症诊断率和促进癌症治疗研究排在首位，而巴基斯坦应答者则将对癌症的知晓和提高疾病诊断率并促进癌症治疗研究排在首位。然而，有关机遇，他们提及最多的都是从改善专业癌症教育和培训中获得帮助。 结论 . 我们发现，绝大多数参加在中国、印度和巴基斯坦召开的临床研究研讨会的年轻肿瘤科医生有提高临床肿瘤研究、专业教育和对癌症的认知的需求。决策制定者在为减少全球癌症负担提供支持、确定卫生保健政策和预算的优先级时，有必要了解本国卫生保健工作人员的特定需求和志愿。 The Oncologist 2015;20:532–538